PENGEMBANGAN PEMBENTUKAN JEJARING DALAM PENGEMBANGAN KEPARIWISATAAN DI TEGALBALONG - Kurniawati, Lucia; Diva, Maria Angela; Yuniarto, Albertus Yudi; Adinata, Patrick Vivid; Hardanti, Yuliana Rini; Ernawati, Maria Theresia (Universitas Sanata Dharma, 2023)
Tourism is considered as a interrelated system consisting of many components which are related to each other. In this case, it is impossible for a tourism provider to provide the tourism product by itself. There should be a partnership developed among many suppliers so that the tourism product has more variety. The community of Tegalbalong should do the same thing. The steps start from the USP of tourism in Tegalbalong because it will define the kind of tourism product that will be offered. Then it also defines the ones who will be invited in partering with Tegalbalong community.